Oral health and elite sport performance. Issue 1 (28th September 2014) - Needleman, Ian; Ashley, Paul; Fine, Peter; Haddad, Fares; Loosemore, Mike; de Medici, Akbar; Donos, Nikos; Newton, Tim; van Someren, Ken; Moazzez, Rebecca; Jaques, Rod; Hunter, Glenn; et al.
Abstract : While the research base is limited, studies have consistently reported poor oral health in elite athletes since the first report from the 1968 Olympic Games. The finding is consistent both across selected samples attending dental clinics at major competitions and more representative sampling of teams and has led to calls from the International Olympic Committee for more accurate data on oral health. Poor oral health is an important issue directly as it can cause pain, negative effects on appearance and psychosocial effects on confidence and quality of life and may have long-term consequences for treatment burden. Self-reported evidence also suggests an impact on training and performance of athletes. There are many potential challenges to the oral health of athletes including nutritional, oral dehydration, exercise-induced immune suppression, lack of awareness, negative health behaviours and lack of prioritisation. However, in theory, oral diseases are preventable by simple interventions with good evidence of efficacy. The consensus statement aims to raise awareness of the issues of oral health in elite sport and recommends strategies for prevention and health promotion in addition to future research strategies.